Environmental Factors Influencing Green Consumer Behaviour in the Digital Age Among the Millennial Generation - Sutedjo Dharma Oetomo , Budi; Santoso, Singgih (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
In Indonesia, millennials’ awareness of environmental conservation is increasing, with social media serving as the main channel to promote sustainable development. However, a gap remains between awareness and actual green purchase behavior. Limited research has examined the link between buying environmentally friendly products and the role of social media in influencing millennial behavior. This study investigates how social media marketing, price perception, and environmental awareness shape attitudes toward green products and, ultimately, the intention to purchase them. Using a survey method with purposive random sampling, respondents were highly educated, active social media users, and residents of the Special Region of Yogyakarta. Data were collected via Google Forms and analyzed using structural equation modeling (SEM). The majority of respondents, aged 20–21, were active on social media but had limited knowledge of green products available in the market. High prices and limited availability were perceived as the main barriers to purchase. Waste, pollution, and global warming were identified as the most urgent environmental issues in Indonesia. Based on results showed that environmental awareness and social media marketing significantly influenced consumer attitudes, whereas price perception did not. This suggests millennials still perceive green products as more expensive than conventional ones, consistent with market realities. Nevertheless, creative social media content on platforms like Instagram and TikTok can effectively encourage millennials, as their environmental awareness is growing. Furthermore, a positive attitude toward green products significantly affects green purchase intention, with climate change awareness motivating young people to adopt environmentally responsible practices.